Budidaya Ayam Kampung Penghasil Telur yang Tinggi Kandungan Vitamin D3 Sebagai Upaya Mencegah Stunting di Desa Pekunden Kabupaten Banyumas - Elly Tugiyanti; Ismoyowati, Ismoyowati; Rosidi, Rosidi; Suswoyo, Imam (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
Stunting remains a serious problem in Indonesia. One of the contributing factors to stunting is the low level of nutritional intake, both in pregnant women and children. Eggs are a nutritious food that is relatively inexpensive, affordable, easy to obtain, and easy to prepare, and is effective in preventing the risk of stunting in young children. Most people in Pekunden village have to buy eggs to consume them. Therefore, through socialization and guidance on cultivating egg-laying native chickens with high vitamin D3 content, it is one of the efforts to reduce stunting cases among the people in Pekunden village, Banyumas district. The community service activities were carried out starting from counseling, feed formulation practice, battery cage making practice, and maintenance. The counseling and practice activities were carried out at the home of one of the residents, Mr. Martono. The counseling session was attended by 19 people, and the feed formulation practice was followed by 12 people, the cage making practice by 11 people, and the cultivation practice by 15 people. A schedule of attendance and management was made for the practice of cultivating native chickens, and the eggs produced were distributed evenly in turn. When the community service was carried out, 30 laying hens (aged 22 weeks) had started producing 2 eggs. After the chickens were 28 weeks old, egg production had reached 14-15 eggs, so all participants in the community service had received eggs evenly. The rest were collected and sold to buy chicken feed.